INTERFERENCE VS ENHANCEMENT : WORK-LIFE BALANCE DIMENSIONS ON JOB SATISFACTION AND TURNOVER INTENTION - Lau, Karuna; Marianti, Maria Merry (LPPM STIE Muhammadiah Bandung, 2024)
The increase in jobs at software development companies has in-creased much faster than the average for other jobs. Intention to change jobs is one of the bad work-related outcomes for software development companies. Work-life balance has been found to reduce the intention in changing jobs. Individuals who have balanced work and life will experience less work overload and depression, and find it easier to carry out work and life roles. This research aims to determine the influence of work-life balance dimensions and job satisfaction on turnover intention. The research method used was descriptive and quantitative involving 61 respondents (saturated sample), and was conducted from December 2022 to April 2023. The sampling technique used was non-probability sampling with a saturated sample or census. Data processing and analysis techniques use PLS-SEM via SmartPLS 3.0 software. The results of the research produced several conclusions, namely two dimensions representing work-life balance that have a significant effect, namely personal life interference with work (PLIW) which is detrimental to job satisfaction, and work interference with personal life (WIPL) which has a positive effect on turnover intention. job satisfaction has a significant negative effect on employee turnover intentions. The step that companies need to take is to pay attention to work interference with personal life, especially related to fatigue after working during peak workload periods. Companies can provide facilities in the form of multivitamins to employees and carry out regular weekly sports activities to increase employee stamina.